Anaerobic co-digestion of lipid-spent microalgae with waste activated sludge and glycerol in batch mode. (May 2015) - Neumann, P.; Torres, A.; Fermoso, F.G.; Borja, R.; Jeison, D.
Abstract: Anaerobic co-digestion of lipid-spent Botryococcus braunii (LSBB) with waste activated sludge (WAS) and glycerol was studied. Different co-digestion mixtures were assessed in biochemical methane potential tests, performed at mesophilic temperature (35 °C). The experimental methane yields obtained were compared to theoretical values calculated from the methane individual yields. No significant increase in BMP was observed when mixing these substrates. A first-order exponential kinetic model was used to obtain the apparent kinetic constant of the processes assayed. The kinetic constant value of the mixture 25% WAS–75% LSBB was 116%, 16% and 43% higher than for WAS, LSBB and glycerol alone, respectively. Highlights: Co-digestion of lipid-spent microalgae with sewage sludge and glycerol was studied. Co-digestion did not induce significant increases in methane yield. Microalgae-sludge mixture at 3:1 ratio induced the highest CH4 production rate.